Transformasi Teknologi E-Commerce Sebagai Upaya Meningkatkan Daya Saing UMKM Di Kota Palangka Raya: Faktor Pendorong Dan Penghambat Adopsi - Dicky Perwira Ompusunggu; Yelin Triani (Pusat Riset dan Inovasi Nasional, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in justice, increase people's income and encourage Indonesia's economic growth. However, in Palangkaraya City, especially during the Covid-19 pandemic, the contribution of MSMEs to improving the economy and people's income has not been proportional to the number. Therefore, this study aims to identify the factors driving and inhibiting the adoption of e-commerce technology among MSMEs in Palangkaraya City. In this study, researchers cite relevant literature and research sources to reveal the factors supporting or hindering e-commerce adoption among MSMEs. Consumer Support, Organizational Support, Knowledge Support, Technical Barriers, Financial Barriers, Legal Barriers, and Regulatory Barriers. The findings of this study can provide insights and recommendations to stakeholders to increase the competitiveness and market access of MSMEs in the digital era.